Hubungan Antara Tendensi Smartphone Addiction dengan Perilaku Phubbing pada Mahasiswa Universitas Bhayangkara Jakarta Raya: Inggrid Margaretha, Fathana Gina - Inggrid Margaretha; Fathana Gina (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2023)
The very rapid development of technology certainly provides various conveniences for its users, but on the other hand it can also have a negative impact if it is not used wisely, one of which is phubbing behavior. Phubbing behavior is related to the tendency of smartphone addiction. Phubbing is an individual who looks at his smartphone when interacting with the other person, while the tendency of smartphone addiction is an addictive behavior on a smartphone which will become a social problem such as withdrawing from the social environment. This study aims to determine the relationship between smartphone addiction tendencies and phubbing behavior among students at Bhayangkara University, Jakarta Raya. The subjects used in this study were 105 active students at Bhayangkara Jakarta Raya University. This research is correlational with qualitative research methods. The sampling technique used is incidental/accidental sampling. The results of this study show that based on the categorization test, there is a tendency for smartphone addiction and phubbing behavior of Bhayangkara University Jakarta Raya students to be in the high category. The results of the correlation test showed a significant relationship between the tendency of smartphone addiction with phubbing behavior with a strong relationship strength.